Pelatihan Baca Al-Qur’an dengan Menggunakan Metode Sorogan Pada Santri Madrasah Diniyah Darul Ihsan Didukuh Tengah, Desa Nambangrejo, Kabupaten Ponorogo - Kharisma Nila Rusiana; Khafidhoh Khafidhoh (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This mentoring was motivated by students of Madin Darul Ihsan who have not been able to apply the correct makharijul huruf and tajwid rules and are still arbitrary in reading the Qur'an. This is because the students have not received guidance on this matter. Thus, the traditional sorogan method is still very much needed to be used to improve the ability to read the Qur'an. The research method used is qualitative with the ABCD approach with existing asset developers. Data collection techniques are carried out through observation, interviews, and documentation. The results of this mentoring are that students of Madin Darul Ihsan have been able to start applying makharijul huruf and reading it better according to the rules of tajwid. This understanding can be seen from students who have read the Qur'an, can understand the laws of nun sukun and tanwin, and can apply makhirijul huruf according to where they come out. The application of the sorogan method in Madin Darul Ihsan can be a solution to this problem. Although this is a traditional method, this method is still very effective for all ages. Departing from this background, this assistance wants to know the improvement of the ability to read the Qur'an through the sorogan Qur'an method at Madin Darul Ihsan. So, the author conducted a study in the form of the title of assistance in reading the Qur'an using the sorogan method.